The Effects of Skill and Physical Exercises on Developing the Explosive Power and Agility of Youth Basketball Players Defensive Skills - Alaa Mohsen Al-Taee, Hussain (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at elaborating and identifying skill – physical exercises on the development of the explosive power and agility of the basketball defensive skills. The sample of the study was determined through youth players in the National Center for Sport Talent Care of Basketball (2018-2019), at ages ranging from 16 to 17 years old. The researcher used some tests, tools and assistive devices to assist him in completing the research, and he adopted the curriculum prepared by the coach, through which the researcher introduced the proposed curriculum within the applied aspect in the training module. The proposed training curriculum included special exercises for 8 weeks, starting from 09/03/2019 to 12/05/2019, and by 3 training modules per week. The most important conclusions reached by the researcher are the emergence of significant differences in the post tests of the explosive power and agility of defensive skills. The most important recommendations of the researcher are the use of special exercises, which showed positive results, the use of new methods and techniques in training in order to develop the game.